THE EFFECT OF EXTRINSIC MOTIVATIONAL FACTORS TOWARDS IBA STUDENT ACHIEVEMENT - Rondonuwu, Mariska; Saerang, David Paul Elia; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
The reason students can facing the world of competition because they have a motivation. A thing that help students to get their motivation when they are not get a motivation by themself is through extrinsic motivational factors. There are two objectives of this research are to analyze the effect of extrinsic motivational factors towards student achievement and to identify the most influental factors on student achievement. The method is multiple linear regression analysis to examine the effect of independent variable (Environment, Lecturer, Family, Study Group) on the dependent variable (student achievement). IBA students in Economics and Business Faculty, Sam Ratulangi University as the population with 100 respondents. The result of this analysis which extrinsic motivational factors have positive effects on student achievement and lecturer is the most influencing variable that significantly influence student achievement. Moreover, based on F-test and T-test, all independent variable influence student achievement simultaneously but not partially because family factor has no significant affect to student achievement. This study suggest thatÂ the IBA system better to keep and maintain enthusiastic lecturer and family factor better to be increased Â to make students can keep to be motivated more. Keyword: student achievement, environment, lecturer, family, study group.